Determinants Of Menstrual Hygiene Among Adolescent Girls: A Multivariate Analysis - Ray , Sudeshna; Dasgupta , Aparajita (National Journal of Community Medicine, 2012)
Background: Menstrual hygiene is an issue that is insufficiently acknowledged. Lack of adequate privacy and sanitation of toilets for school girls; make them vulnerable to mental, emotional and physical problem especially during their menstruating days. Objectives: To identify the issues and challenges of menstruation faced by the adolescent girls, to determine the factors behind the existing practices of menstrual hygiene and to find out the proportion of the study population complaining of symptoms related to genitourinary tract and related health care seeking behavior. Methods: A descriptive, cross-sectional study was conducted among 190 adolescent girls of a rural secondary school of West Bengal. Results: Out of 190 respondents, 80(42%) girls were aware about menstruation prior to attainment of menarche. After bivariate analysis, the significant risk factors of good menstrual hygiene were entered into the multivariate model. It revealed that good menstrual hygiene was more among those whose mothers were literate [AOR 2.3 (1.06-5.01)], girls studying in more than grade X in school [AOR 2.71(1.16-6.35)],having prior knowledge about menstruation before menarche [AOR 2.97(1.29-6.85)],usage of proper sanitary latrine at home [AOR 3.14(1.42-6.00)] and exposure to advertisements promoting usage of sanitary towels in mass media[AOR-2.52(1.10-5.70). Conclusions: Adoption of high quality menstrual hygiene will play an important role in prevention of RTI and Cancer of cervix among the women population. Therefore promoting positive attitudes towards management of menstruation and related problems among the adolescent girls is the need of the hour.